The evolution of tax burden and tax effort in the OECD between 2000 and 2015 - Cavadas, Maria João Barros Alves (2018)
Fiscal policies are one of the main concerns of any government. Balancing the decisions regarding public expenditure and how that expenditure is to be financed is paramount to allow for a favourable level of welfare in a society. The expenditure side is dependent upon the collection of revenues that can finance the government’s expenses. These revenues come mostly from taxes. Therefore, taxation plays a pivotal role in a society, and it is the focus of this dissertation. Greater attention is paid to what can be considered measures of the level of taxation of a country – tax burden and tax effort. There is great deal of concepts attached to taxation, hence the necessity to have them defined and explained in order to make any further analyses. A systematic literature review is performed to study the investigation on taxation since 1972. A database of data for 35 of the 36 countries of the OECD is used to compute the three aforementioned metrics, which are then analysed and compared between them. An alternative measure of tax effort (the World Tax Index) is briefly described, since it is a breakthrough in the field. The development of new metrics in future investigation is proposed.